2021
DOI: 10.1002/acn3.51383
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of viral and autoimmune central nervous system inflammation by kynurenine pathway

Abstract: Objective: To determine whether the metabolites of Kynurenine pathway (KP) could serve as biomarkers for distinguishing between viral CNS infections and autoimmune neuroinflammatory diseases, especially anti-N-methyl-D-aspartate receptor encephalitis (NMDARE) and herpes virus encephalitis (HSE). Methods: This study enrolled CSF samples from 76 patients with viral CNS infections, autoimmune neuroinflammatory, and non-inflammatory neurological diseases. We measured cerebrospinal fluid (CSF) concentrations of try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Using LC-MS/MS analysis of the same cohort, we have previously reported that CSF kynurenine and the tryptophan/kynurenine ratio constitute biomarkers for the differentiation between viral CNS infections and autoimmune neuroin ammation (14), which was subsequently corroborated using a simple immunoassay for these analytes (29). Kynurenine was studied in ( 14) because it had been detected > LOD preferentially in infected samples, but it was excluded from the present analysis because it was detected > LOD in < 80% of the samples.…”
Section: Discussionmentioning
confidence: 87%
“…Using LC-MS/MS analysis of the same cohort, we have previously reported that CSF kynurenine and the tryptophan/kynurenine ratio constitute biomarkers for the differentiation between viral CNS infections and autoimmune neuroin ammation (14), which was subsequently corroborated using a simple immunoassay for these analytes (29). Kynurenine was studied in ( 14) because it had been detected > LOD preferentially in infected samples, but it was excluded from the present analysis because it was detected > LOD in < 80% of the samples.…”
Section: Discussionmentioning
confidence: 87%
“…Using LC–MS/MS analysis of the same cohort, we have previously reported that CSF kynurenine and the tryptophan/kynurenine ratio constitute biomarkers for the differentiation between viral CNS infections and autoimmune neuroinflammation [ 18 ], which was subsequently corroborated using a simple immunoassay for these analytes [ 33 ]. Kynurenine was studied in [ 18 ] because it had been detected > LOD preferentially in infected samples and therefore held promise as a biomarker for infectious CNS processes, but it was excluded from the present analysis because it was detected > LOD in < 80% of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) is a qualitative and quantitative detection method, using antigen–antibody binding specificity ( 37 ). One study measured CSF concentrations of tryptophan (Trp) and kynurenine (Kyn) using ELISA in 76 patients and found that Kyn concentrations and Kyn/Trp ratio were highly increased in viral CNS infections, while patients with autoimmune neuroinflammatory and non-inflammatory diseases showed low concentrations ( 38 ). Day et al ( 39 ) performed ELISA to detect enterovirus-specific IgM in serum samples from 557 patients clinically diagnosed with meningitis or encephalitis and found that the detection rate was much higher than the virus isolation rate.…”
Section: Etiological Examinationmentioning
confidence: 99%